Thalamic neurometabolic alterations in tremulous Parkinson's disease: A preliminary proton MR spectroscopy study. (October 2017) - Barbagallo, Gaetano; Arabia, Gennarina; Morelli, Maurizio; Nisticò, Rita; Novellino, Fabiana; Salsone, Maria; Rocca, Federico; Quattrone, Andrea; Caracciolo, Manuela; Sabatini, Umberto; Cherubini, Andrea; Quattrone, Aldo
Abstract: Introduction: The objective of this study was to investigate the thalamic biochemical changes in tremor-dominant Parkinson's disease (tPD) patients in comparison with essential tremor with resting tremor (rET) patients, by using proton MR spectroscopy ( 1 H-MRS). Methods: Fourteen tPD patients, 12 rET patients and 10 controls participated in this study. All patients underwent dopamine transporter single-photon emission computed tomography (DAT-SPECT) with 123 I-ioflupane, and a short-echo single-voxel 1 H-MRS on a 3T scanner. A voxel of 10 × 15 × 10 mm involving the Vim nucleus was acquired in both thalami of all subjects. Peak areas of N -acetyl-aspartate (NAA), creatine (Cr), glycerophosphocholine (Cho), and glutamate (Glu) were measured for each voxel using LCModel. The NAA/Cr, Cho/Cr, and Glu/Cr ratios were then calculated. Results: DAT-SPECT was abnormal in tPD patients, whereas it was normal in rET patients. Patients with tPD showed a significant reduction of NAA/Cr and Cho/Cr in the thalami compared to rET and healthy controls; whereas there were no significant differences between rET patients and controls. The combination of thalamic NAA/Cr and Cho/Cr ratios showed a 100% accuracy in distinguishing tPD patients from rET patients and controls. Conclusions: This study provides preliminary evidence that thalamic neurometabolic abnormalities occur in tremor-dominant phenotype of PD, and suggests that 1 H-MRS can help differentiate patients with tPD from those with rET. Highlights: 1 H-MRS is able to detect in vivo neurometabolic alterations in brain tissue. We found thalamic biochemical changes in tPD patients. Thalamic 1 H-MRS may help differentiate tPD from rET patients.